Characterization of Halophilic Inulinase Producing Strains of Bacillus and Klebsiella Species Isolated From the Salt Mines of Pakistan. Issue 7 (1st July 2022) - Ullah, Hamid; Khan, Hassan; Haider, Shabeer; Shehzad, Aamir; Anees, Muhammad
Abstract: Halophiles are excellent sources of enzymes which are not only salt stable but also perform catalysis under extreme reaction conditions. The habitat of salt mines and its microbial diversity have not been thoroughly explored. In the present study, seven halophilic inulinase-producing bacteria (H1N1–H1N7) were isolated from the Bahadarkhel salt mines of Pakistan, and were identified based on their morphological, biochemical and molecular features. The strains H1N3, H1N4, H1N6, H1N7 were capable of growing at 20% salt concentration and therefore were considered as extremely halotolerant. Inulinase activities of the isolates were detected in inulin-containing broth media, and were further confirmed on inulin-based agar plates. The strains HIN1, H1N3, H1N5, and H1N7 exhibited the maximum zone of clearance (≥15 mm) on inuline agar medium. The strain H1N1 showed the highest zone of clearance of 19 mm. Morphological, biochemical and molecular characterization showed that the inulinase producing isolates were related to Bacillus and Klebsiella genera. The molecular identification was based on 16S rRNA gene sequencing. The strain H1N2 was capable of producing the four tested halozymes including inulinase, amylase, protease, and lipase. The strains HIN3, HIN4, and H1N5 were capable of producing three halozymes, i.e., inulinase, amylase, and protease while the strains H1N6 and H1N7 produced inulinases, lipases and proteases. These salt tolerant bacterial strains exhibiting diverse enzyme characteristics and phylogeny could be highly useful for future practical applications.